Epiphytic algal flora associated with habitat-forming brown seaweed in a central Mediterranean coastal area (Conero Riviera, Adriatic Sea): diversity and relationship with environmental variables - BELLANTI, GIULIA; ROMAGNOLI, TIZIANA; ACCORONI, STEFANO; CAMPANELLI, ALESSANDRA; TOTTI, CECILIA; RINDI, FABIO (Mediterranean Marine Science, 2024)
The Cystoseira s.l. complex includes the most common macrophytes in shallow sublittoral habitats of Mediterranean rocky shores, where they form marine forests providing valuable ecosystem services. These communities are considered to be repositories of great marine biodiversity, but the epiphytic assemblages associated with them are still not fully known. In particular, extremely limited information is available about their microalgal epiphytes. We examined the microepiphytic and macroepiphytic communities associated with the brown alga Gongolaria barbata in a coastal area of the central Adriatic shore (Conero Riviera, Italy). We recorded 119 microalgal taxa and 60 macroalgal taxa growing as epiphytes on this species. Diatoms were the dominant microepiphytes, accounting for 83% of the total number of taxa, followed by Dinophyceae (9%), unidentified phytoflagellates (4%) and Cyanobacteria (3%). A slight negative and positive correlation was observed between phytoflagellate abundance and water temperature and DIN (Dissolved Inorganic Nitrogen). Red algae represented the majority of the macroepiphytes recorded, accounting for 60% of the total. Most of the macroalgal epiphytes were ephemeral species with filamentous morphology, and the non-indigenous red alga Melanothamnus japonicus was among the most common epiphytes. Our results confirm the role of the Cystoseira s.l. species as a major repository of marine biodiversity in the Mediterranean. However, they also suggest that our understanding of the diversity of their associated communities is probably still largely incomplete. New studies combining traditional taxonomy and DNA metabarcoding will be essential to advance our knowledge of them.